2020
DOI: 10.1177/1747021820940223
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic and phonological activation in Hong Kong deaf readers: An eye-tracking study

Abstract: We used an error disruption paradigm to investigate how deaf readers from Hong Kong, who had varying levels of reading fluency, use orthographic, phonological, and mouth-shape-based (i.e., “visemic”) codes during Chinese sentence reading while also examining the role of contextual information in facilitating lexical retrieval and integration. Participants had their eye movements recorded as they silently read Chinese sentences containing orthographic, homophonic, homovisemic, or unrelated errors. Sentences var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
3
8
1
Order By: Relevance
“…In contrast, deaf writers were boosted in structural priming when the homophone verbs were identical in orthography but not when they differed. These results are, on the one hand, consistent with previous findings that deaf writers are especially sensitive to orthographic information in reading (Bélanger et al, 2012(Bélanger et al, , 2013Fariña et al, 2017;Thierfelder et al, 2020a; and extend this conclusion to production. On the other hand, the results suggest that, despite findings that some deaf individuals access speech-based phonological representations in Chinese word reading (e.g., Thierfelder et al, 2020a;G.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, deaf writers were boosted in structural priming when the homophone verbs were identical in orthography but not when they differed. These results are, on the one hand, consistent with previous findings that deaf writers are especially sensitive to orthographic information in reading (Bélanger et al, 2012(Bélanger et al, , 2013Fariña et al, 2017;Thierfelder et al, 2020a; and extend this conclusion to production. On the other hand, the results suggest that, despite findings that some deaf individuals access speech-based phonological representations in Chinese word reading (e.g., Thierfelder et al, 2020a;G.…”
Section: Discussionsupporting
confidence: 92%
“…These results are, on the one hand, consistent with previous findings that deaf writers are especially sensitive to orthographic information in reading (Bélanger et al, 2012(Bélanger et al, , 2013Fariña et al, 2017;Thierfelder et al, 2020a; and extend this conclusion to production. On the other hand, the results suggest that, despite findings that some deaf individuals access speech-based phonological representations in Chinese word reading (e.g., Thierfelder et al, 2020a;G. Yan et al, 2020;, syntactic choices in written language production are not influenced by the extent to which prime and target verbs share spoken phonology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, R. Wang et al, (2020) showed that, Chinese speakers are quicker at handwriting a Chinese character if the character has more regularity between its pronunciation and orthography (see more evidence below). For deaf speakers, there is evidence that they may have some (though limited) access to spoken language representations and these representations are activated in reading (Gutierrez-Sigut, Vergara-Martínez, & Perea, 2017;Hanson, 1989;Thierfelder, Wigglesworth, & Tang, 2020b;Wang, Trezek, Luckner, & Paul, 2008; see Mayberry, Del Giudice, & Lieberman, 2011, for a meta-analysis). For instance, in a lexical decision task, Gutierrez-Sigut et al (2017) showed that deaf readers (as hearing readers) were quicker at responding to a target (e.g., CORAL) preceded by a masked pseudo-homophone prime (e.g., koral) than by a masked orthographic control (e.g., toral).…”
Section: Written Language Production By Deaf Speakersmentioning
confidence: 99%
“…What is much less clear is whether deaf speakers may be influenced by wordform (phonological and orthographic) information from prior language use. Regarding phonological influence, there is evidence that deaf speakers who do not produce spoken language nonetheless have some access to phonological representations in reading (e.g., Gutierrez-Sigut et al, 2017;Thierfelder et al, 2020b). However, it is also possible that the phonological information deaf speakers have access to is just too little for it to have any influence in written production at all.…”
Section: Syntactic and Lexical Influences On Syntactic Encoding In Written Language Productionmentioning
confidence: 99%